ANALISIS KINERJA PABRIK TEH HITAM Ã¢â‚¬Å“PAHIT MADUÃ¢â‚¬Â - djawardi, djawardi; gunawan, yustiar (Jurnal Sains dan Teknologi Indonesia, 2011)
The business unit's black tea processing of Perkebunan Nusantara suffered a loss of approximately Rp.60 billion. This is caused by the failure to achieve the quality and quantity of production which has been targeted by the management. Black tea processing factory "Pahit Madu" is required to improve the performance of the production process. To improve the production of black tea starts from improved production equipment through improved equipment utilization. One method ofmeasuring the effectiveness of using an apparatus is Overall EquipmentEffectiveness (OEE). OEE calculation results show that black tea factory "Pahit Madu" for four (4) years under the standard. Means, the effectiveness of utilization of equipment in the factory black tea "Pahit Madu" was still very low. This was shown by the low performance equipment in the milling unit, drying unit and sortation unit. Toimprove the performance of the plant should begin by increasing the Cutting Tearing Curling (CTC) machine in milling stations, machines Fluid Bed Dryer (FBD) and Heat Exchanger (HE) at the drying stations, and Winnower machines at the sortation stations.